تحليل تصورات طلبة كلية التربية-جامعة الأزهر لبيئة التعلم الذكية المفضلة - حسن، أحمد محمد شبيب (مجلة التربية : مجلة علمية محكمة للبحوث التربوية و النفسية و الاجتماعية., 2022)
أصبحت بيئة التعلم الذكية هي التي يمكن للمعلمين والطلاب أن يمارسوا فيها خبرات وتجارب تعليمية غنية لم يسبق لها مثيل من قبل، لذلك فقد كشفت العديد من الأبحاث العلاقة بين مهارات التعلم ونتائج التعلم وبيئات التعلم الذكية، والبعض الأخر كان مهتما بالتعرف على العلاقة بين بيئات التعلم الذكية ومهارات تعلم الطلاب كبيئة تعليمية مزدهرة في القرن الحادي والعشرين. تكونت عينة البحث من 500 طالبا تم اختيارهم كلية التربية-جامعة الأزهر بالقاهرة من الفرقة الثانية والمختارين من الشعب الأتية (العلمية-الأدبية-والنوعية) والفرقة الرابعة المختارين أيضا من الشعب (العلمية والأدبية والنوعية). ولتحقيق هدف البحث تم إعداد مقياس يهدف إلى قياس بيئة التعلم الذكية المفضلة يتكون من (46) عبارة موزعة على عشر أبعاد تمثل بيئة التعلم الذكية. أشارت النتائج إلى: -أن تفضيلات الطلاب لبيئة التعلم الذكية على أبعاد المقياس كانت جميعها مرتفعة، وهذا يشير أن الطلاب يفضلون التعلم في ظل بيئة تعلم ذكية غنية بالتكنولوجيا بأبعادها موضوع البحث المدروس. -عدم وجود فروق ذات دلالة إحصائية في استجابات عينة البحث على أبعاد المقياس تبعا للفرقة الدراسية (الثانية-الرابعة) عدا بعدى التصميم المادي وبيانات التعلم. -وجود فروق ذات دلالة إحصائية في استجابات عينة البحث على أبعاد المقياس تبعا لمتغير التخصص (علمي-أدبي-نوعي) وهذه الفروق لصالح التخصص النوعي، وتم الخروج بمجموعة من التوصيات التربوية المناسبة. The smart learning environment has become one in which teachers and students can practise rich learning experiences that have never been seen before. therefore, many types of research have revealed the relationship between learning skills and learning outcomes and smart learning environments, and some were interested in revealing the relationship between smart learning environments and student learning skills as a flourishing learning environment in the twenty-first century. the research sample consisted of 500 students who were selected from the college of education -al Azhar University in Cairo from the second year and chosen from the following departments (scientific-literary-and qualitative) and the fourth year also selected from the departments (scientific, literary and qualitative). to achieve the aim of the research, a scale was prepared that aims to measure the preferred smart learning environment, consisting of (46) phrases distributed over ten dimensions that represent the smart learning environment. the results indicated that: -students' preferences for the smart learning environment on the dimensions of the scale were all high, and this indicates that the students prefer learning in light of a smart learning environment rich in technology in terms of its dimensions, the subject of the studied research. -there were no statistically significant differences in the responses of the research sample on the dimensions of the scale according to the study year (second-fourth), except for the dimensions of physical design and learning data. -there were statistically significant differences in the responses of the research sample on the dimensions of the scale according to the specialization variable (scientific-literary-qualitative) and these differences were in favor of the qualitative specialization, and a set of appropriate educational recommendations were produced.